DIAGNOSTIC TOOLS FOR DETERMINING POSTURAL CONTROL IN PATIENTS WITH A NEUROLOGICAL PROFILE - Лістау, Карина; Собко, Діана (SWorldJournal, 2024)
Modern data of scientific research claim that the first and most important part of the rehabilitation process is the examination. In the description of the professional activity of the "Physical therapist" specialty of the International Standard Classifi